Expediente (Revista do Tribunal Regional Federal da 3ª Região, 2023)
DIRETOR DA REVISTA:Desembargador Federal Souza RibeiroASSESSORA:Simone de Alcantara SavazzoniEQUIPE:André Luiz Porreca Ferreira CunhaRenata Bataglia GarciaSilvio Pires de QueirozCAPA:Paulo Polimeno
Keywords: v. 34; n. 157; jan./mar. 2023